Development of a Positive Youth Development Program: Promoting the Mental Health of Stressful Adolescents Using Principles of Problem Solving Therapy - Daniel T.L. Shek; Joyce T.W. Chow (The Scientific World Journal)
This paper outlines the proposal for the development, implementation, and evaluation of a positive youth development program that attempts to promote the mental health of stressful Chinese adolescents using principles of Problem Solving Therapy (PST). There are two general aims of PST: to help clients identify life difficulties and resolve them, as well as to teach them skills on how to deal with future problems. The proposed project will utilize the principles of PST as the guiding framework to run two mental health promotion courses for adolescents who are experiencing disturbing stressful responses and students who want to improve their stress management style. Both objective and subjective outcome evaluation strategies will be carried out to assess the effectiveness of the intervention to promote the psychological well-being in adolescents who are experiencing stress. A related sample proposal is described that can give social workers some insight on how to prepare a proposal for developing the Tier 2 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programs).